2013
DOI: 10.1002/ldr.2223
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Seasonality in Estimating the C‐Factor of Soil Erosion Studies

Abstract: Monitoring soil erosion risk is an important part of soil conservation practices. It is usually estimated with the Universal Soil Loss Equation, and the C‐factor (vegetation cover) is derived from optical satellite images. However, because of lack of data and resources, or in rapid assessments, C‐factor is estimated using one or a few satellite observations, despite being temporally variable according to plants' phenology. The aim of this work was to study the effect of seasonality in estimating C‐factor. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 35 publications
(41 reference statements)
0
54
0
3
Order By: Relevance
“…C " expp´aˆN DV I b´NDV I˙ ( 9) Previous studies indicated that seasonal variations of the Normalized Difference Vegetation Index (NDVI) could strongly influence the estimated soil erosion rate [18,71]. However, the heavy cloudiness problem in the tropical rainforests and mountain areas of the country [18,26] made it nearly impossible to retrieve the dynamic of NDVI and land cover change with satellite data for a whole year.…”
Section: Discussionmentioning
confidence: 99%
“…C " expp´aˆN DV I b´NDV I˙ ( 9) Previous studies indicated that seasonal variations of the Normalized Difference Vegetation Index (NDVI) could strongly influence the estimated soil erosion rate [18,71]. However, the heavy cloudiness problem in the tropical rainforests and mountain areas of the country [18,26] made it nearly impossible to retrieve the dynamic of NDVI and land cover change with satellite data for a whole year.…”
Section: Discussionmentioning
confidence: 99%
“…For a better understanding of soil erosion processes caused by crop changes and their effects in larger areas, it is important to increase the experimental monitoring areas in both spatial and temporal scales [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, from NDVI values, some methods have been developed to estimate the Rusle C factor (Knijff et al, 1999;Asis & Omasa, 2007;Durigon et al, 2014). These methods are developed from regression models which correlate C factor values, either measured in the field or obtained from other studies, to NDVI values generally obtained from TM sensor on Landsat 5, or by the moderate resolution imaging spectroradiometer (Modis) data (Schönbrodt et al, 2010;Le et al, 2012;Alexandridis et al, 2013;Bargiel et al, 2013). However, under tropical climate conditions, the C factor tends to be higher than that calculated by these methods for the same vegetation cover.…”
Section: Introductionmentioning
confidence: 99%